Deep culturing the fecal microbiota of healthy laying hens - Zhixuan Feng; Natalia Lorenc; Bridget O’Brien; Guangwen Sun; Zhiwei Li; Dongyun Jung; Jennifer Ronholm (Animal Microbiome)
Abstract Background The microbiota is implicated in several aspects of livestock health and disease. Understanding the structure and function of the poultry microbiota would be a valuable tool for improving their health and productivity since the microbiota can likely be optimized for metrics that are important to the industry such as improved feed conversion ratio, lower greenhouse gas emissions, and higher levels of competitive exclusion against pathogens. Most research into understanding the poultry microbiota has relied on culture-independent methods; however, the pure culture of bacteria is essential to elucidating the roles of individual bacteria in the microbiota and developing novel probiotic products for poultry production. Results In this study, we have used a deep culturing approach consisting of 76 culture conditions to generate a culture collection of 1,240 bacterial isolates from healthy chickens. We then compared the taxonomy of cultured isolates to the taxonomic results of metagenomic sequencing to estimate what proportion of the microbiota was cultured. Metagenomic sequencing detected DNA from 545 bacterial species while deep culturing was able to produce isolates for 128 bacterial species. Some bacterial families, such as Comamonadaceae and Neisseriaceae were only detected via culturing – indicating that metagenomic analysis may not provide a complete taxonomic census of the microbiota. To further examine sub-species diversity in the poultry bacteriome, we whole genome sequenced 114 Escherichia coli isolates from 6 fecal samples and observed a great deal of diversity. Conclusions Deep culturing and metagenomic sequencing approaches to examine the diversity of the microbiota within an individual will yield different results. In this project we generated a culture collection of enteric bacteria from healthy laying hens that can be used to further understand the role of specific commensals within the broader microbiota context and have made this collection available to the community. Isolates from this collection can be requested by contacting the corresponding author and will be provided at cost.